Observer-based control design for switched affine systems and applications to DC-DC converters - Yoshimura, Victor Leonardo; Assunção, Edvaldo [UNESP]; Da Silva, Emerson Ravazzi Pires [UNESP]; Teixeira, Marcelo Carvalho Minhoto [UNESP]; Mainardi Júnior, Edson Italo (Springer Nature, 2013)
This paper deals with the problem of establishing a state estimator for switched affine systems. For that matter, a modification on the Luenberger observer is proposed, the switched Luenberger observer, whose idea is to design one output gain matrix for each mode of the original system. The efficiency of the proposed method relies on a simplification on estimation error which is proved always valid, guaranteeing the estimation error to asymptotically converge to zero, for any initial state and switching law. Next, a dynamic output-dependent switching law is formulated. Then, design methodologies using linear matrix inequalities are proposed, which, to the authors's knowledge, have not yet been applied to this problem. Finally, observers for DC-DC converters are designed and simulated as application examples. © 2013 Brazilian Society for Automatics - SBA.
Keywords: DC-DC converters; Linear matrix inequalities; Output feedback; State estimation; Switched affine systems; Switched Luenberger observer; Application examples; Design Methodology; Estimation errors; Luenberger observers; Observer based control; Original systems; Switching networks